PENGARUH PERIZINAN TERHADAP PELAYANAN KANTOR CAMAT NATAL KABUPATEN MANDAILING NATAL - Andrian Syaputra; Imsar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Licensing is a form of granting permission/legality to everyone, whether to carry out business or non-business activities. Licensing is useful for controlling, regulating so that activities carried out by the community do not interfere with the comfort of the surrounding environment, so that relationships are created within the community. This study aims to determine how licensing affects the services of the Natal District Head office located in the district. Christmas Mandailing. The method in this study uses a qualitative method. The results of this study indicate that the effect of licensing on the services of the Natal District Head office has had a good impact. However, there are several things that need to be improved or improved such as communication in granting permits, ethics in granting permits to the public.